2022
DOI: 10.1088/1748-9326/ac8237
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of fire dynamics in and around indigenous territories and protected areas in a Brazilian agricultural frontier

Abstract: Sustainable land management is integral to conserving tropical ecosystems and reducing carbon emissions. Human-set fires are part of the land cover change process and are the most common driver of deforestation and carbon emissions in Amazonia. Analyzing the behavior of major fire events provides insight into the effectiveness of current protections. This study aims to quantify the role of Indigenous Territories and Protected Areas (ITPAs) in characterizing anthropogenic fire regimes over the 2020 fire season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…These authors also reported that the presence of intact landscapes (Human Footprint value < 4) was significantly higher on Indigenous Peoples' lands compared to areas located within 10–50 km of the border of Indigenous Peoples' lands (Estrada et al, 2022). Indigenous Peoples' lands also serve as a buffer against the intensity and spread of fires (Walker et al, 2022). Given their long history of living in the Amazon, knowledge of local ecological processes, and cultural practices of forest succession management, Indigenous Peoples have the potential to play a critical role in the restoration of degraded lands across the Amazon (Schmidt et al, 2021).…”
Section: Indigenous Peoples Are Strong Stewards Of the Environmentmentioning
confidence: 99%
“…These authors also reported that the presence of intact landscapes (Human Footprint value < 4) was significantly higher on Indigenous Peoples' lands compared to areas located within 10–50 km of the border of Indigenous Peoples' lands (Estrada et al, 2022). Indigenous Peoples' lands also serve as a buffer against the intensity and spread of fires (Walker et al, 2022). Given their long history of living in the Amazon, knowledge of local ecological processes, and cultural practices of forest succession management, Indigenous Peoples have the potential to play a critical role in the restoration of degraded lands across the Amazon (Schmidt et al, 2021).…”
Section: Indigenous Peoples Are Strong Stewards Of the Environmentmentioning
confidence: 99%